A model for the extrapolation of the characteristic curves of Pumps as Turbines from a datum Best Efficiency Point. (15th October 2018) - Novara, Daniele; McNabola, Aonghus
Highlights: The proposed model can give a more robust estimate of the full behaviour of PATs. Its empirical coefficients are derived from the largest available PAT curves database. The overall goodness of fit is improved by up to 60%. The effectiveness of PATs was compared to that of other hydro turbines. Abstract: Pumps used as Turbines (PATs) are a viable and low-cost technology of energy converters suitable for small-scale and in-pipe energy generation from water resources. However, amongst the main barriers to PAT technology diffusion is the unavailability of the characteristic curves of most hydraulic pumps on the market when used as turbines. Several methods exist in the literature to derive the shape of head and power characteristic curves of a PAT knowing its Best Efficiency Point (BEP). Such methods based on fixed-coefficient polynomials have been assessed here in a cross-comparison and a new method was developed based on a database of 113 experimentally tested PAT curves, which proved to reproduce the behaviour of the sampled machines more accurately by improving the overall goodness of fit up to 60%, 37% and 5% according to the different selected indicators. Finally, the mechanical efficiency and system efficiency of a PAT under variable flow rates has been compared and contrasted with that of conventional hydro turbines.